2018
DOI: 10.1016/j.coph.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

The present state of the tuberculosis drug development pipeline

Abstract: Tuberculosis now ranks as the leading cause of death in the world due to a single infectious agent. Current standard of care treatment can achieve very high cure rates for drug-sensitive disease but requires a 6-month duration of chemotherapy. Drug-resistant disease requires significantly longer treatment durations with drugs associated with a higher risk of adverse events. Thus, there is a pressing need for a drug regimen that is safer, shorter in duration and superior to current front-line chemotherapy in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 72 publications
1
67
0
Order By: Relevance
“…There is an urgent need for new antimycobacterial agents preferably with novel mechanisms of action in order to tackle drug‐resistant M. tuberculosis infection . This work shows that azaaurones and their N ‐acetyl counterparts represent a new entry in the toolbox of chemotypes capable of inhibiting M. tuberculosis growth.…”
Section: Resultsmentioning
confidence: 96%
“…There is an urgent need for new antimycobacterial agents preferably with novel mechanisms of action in order to tackle drug‐resistant M. tuberculosis infection . This work shows that azaaurones and their N ‐acetyl counterparts represent a new entry in the toolbox of chemotypes capable of inhibiting M. tuberculosis growth.…”
Section: Resultsmentioning
confidence: 96%
“…Studies have shown that the usage of the drug for drug-resistant TB treatment improved sputum conversion and reduced chemotherapy duration and relapse [16][17][18][19]. Hence, new BDQ-containing drug regimens are currently being explored in Phase III clinical trials, such as the STREAM and SimpliciTB trials [20]. One such trial, the Nix-TB trial, resulted in the recent US FDA approval of the BDQ-pretomanid-linezolid six months, all-oral regimen for the treatment of drug-resistant TB [21,22].…”
mentioning
confidence: 99%
“…Those pioneering compounds can lead the way to more valuable therapeutics. Numerous new compounds are being studied that either derive from the known hits or target other biosynthetic pathways of the cell wall [261,262]. In the past 20 years, M. tuberculosis has been unraveling many of its secrets: its niches in the host, its metabolism and its way of fighting drugs.…”
Section: Resultsmentioning
confidence: 99%